2016
DOI: 10.1103/physrevd.94.111501
|View full text |Cite
|
Sign up to set email alerts
|

Next-to-next-to-leading-order QCD corrections to χc0,2γγ

Abstract: We calculate the next-to-next-to-leading-order (NNLO) perturbative corrections to P -wave quarkonia annihilation decay to two photons, in the framework of nonrelativistic QCD (NRQCD) factorization. The order-α 2 s short-distance coefficients associated with each helicity amplitude are presented in a semi-analytic form, including the "light-by-light" contributions. With substantial NNLO corrections, we find disquieting discrepancy when confronting our state-of-the-art predictions with the latest BESIII measurem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 45 publications
1
37
1
1
Order By: Relevance
“…The LDME is determined to be O( 3 PJ ) = 0.060 +0.043 −0.029 GeV 5 [13], which seems to be considerably smaller than the values given by potential models. Nevertheless, the O(α 2 s ) corrections χc0,2 → γγ turns out to be substantial [28]. For consistency, we will not use the fitted value of LDME in [13] for m = 1.68 GeV.…”
Section: Phenomenologymentioning
confidence: 99%
“…The LDME is determined to be O( 3 PJ ) = 0.060 +0.043 −0.029 GeV 5 [13], which seems to be considerably smaller than the values given by potential models. Nevertheless, the O(α 2 s ) corrections χc0,2 → γγ turns out to be substantial [28]. For consistency, we will not use the fitted value of LDME in [13] for m = 1.68 GeV.…”
Section: Phenomenologymentioning
confidence: 99%
“…To date, perturbative calculations beyond NLO have been conducted only for a few exclusive processes involving quarkonium, exemplified by O(α 2 s ) corrections to Υ(J/ψ) → e + e − [11,12] (Notice the O(α 3 s ) coefficients were also available recently [13,14]), η b,c → γγ [15,16], χ c0,2 → γγ [17], and B c → ℓν [18,19], as well as the O(α 2 s ) correction to the γγ * → η c,b transition form factor [16]. Only two-loop virtual corrections are required in calculating these hard matching coefficients, since they correspond to exclusive quarkonium decays or productions.…”
mentioning
confidence: 99%
“…Refs. [5][6][7][8][9][10][11][12][13][14][15][16] and references therein. Within the framework of NRQCD factorization theory, one has observed that the leading-order (LO) prediction is close to the experimental measurements, but this process is extremely sensitive to highorder QCD corrections and relativistic corrections, due to the fact that the typical magnitude of strong coupling constant and the squared relative velocity of the charm quark in charmonium, α s (m c ) ∼ v 2 c ∼ 0.3, are comparatively large.…”
mentioning
confidence: 99%
“…In year 2016, the NNLO QCD corrections to the P-wave charmonium χ c0,c2 → γ γ have been done by Ref. [16], which however show large renormalization scale dependence, and the predicted R-ratio cannot explain the above BESIII value. It is important to show what's the reason for such discrepancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation